CX3CL1-Fc treatment prevents atherosclerosis in Ldlr KO mice - Matthew Riopel; Melanie Vassallo; Erik Ehinger; Jennifer Pattison; Karen Bowden; Holger Winkels; Maria Wilson; Ron de Jong; Sanjay Patel; Deepika Balakrishna; James Bilakovics; Andrea Fanjul; et al. (Molecular Metabolism, 2019)
Objective: Atherosclerosis is a major cause of cardiovascular disease. Monocyte-endothelial cell interactions are partly mediated by expression of monocyte CX3CR1 and endothelial cell fractalkine (CX3CL1). Interrupting the interaction between this ligand–receptor pair should reduce monocyte binding to the endothelial wall and reduce atherosclerosis. We sought to reduce atherosclerosis by preventing monocyte-endothelial cell interactions through use of a long-acting CX3CR1 agonist. Methods: In this study, the chemokine domain of CX3CL1 was fused to the mouse Fc region to generate a long-acting soluble form of CX3CL1 suitable for chronic studies. CX3CL1-Fc or saline was injected twice a week (30 mg/kg) for 4 months into Ldlr knockout (KO) mice on an atherogenic western diet. Results: CX3CL1-Fc-treated Ldlr KO mice showed decreased en face aortic lesion surface area and reduced aortic root lesion size with decreased necrotic core area. Flow cytometry analyses of CX3CL1-Fc-treated aortic wall cell digests revealed a decrease in M1-like polarized macrophages and T cells. Moreover, CX3CL1-Fc administration reduced diet-induced atherosclerosis after switching from an atherogenic to a normal chow diet. In vitro monocyte adhesion studies revealed that CX3CL1-Fc treatment caused fewer monocytes to adhere to a human umbilical vein endothelial cell monolayer. Furthermore, a dorsal window chamber model demonstrated that CX3CL1-Fc treatment decreased in vivo leukocyte adhesion and rolling in live capillaries after short-term ischemia-reperfusion. Conclusion: These results indicate that CX3CL1-Fc can inhibit monocyte/endothelial cell adhesion as well as reduce atherosclerosis. Keywords: Fractalkine, CX3CR1, Atherosclerosis, Monocyte adhesion, Inflammation, Ldlr KO